Virtual audio processing lab using GUI (Graphical User Interface) / Mohd Khairol Fitza Mohamed Daud - Mohamed Daud, Mohd Khairol Fitza (2010)
Recently, the wavelet transform has emerged as a cutting edge technology, within the field of audio compression. Wavelet compression technique provides a good compression scheme for audio processing, which is the current audio technique. In wavelet compression system, the wavelet transform selection and transform coefficient bit allocation procedure are design to take advantage of the masking effect in human hearing. They minimize the number of bits required to represent each frame of audio material at a fixed distortion level. This project studies the different effect of audio compression due to the different audio file, different wavelet families (Haar, Symlet and Daubechies) and different level of decomposition. An audio processing lab is implemented in Graphical User Interface (GUI) using MATLAB software. The audio compression coder is used to compress the signal. The results obtained were analyzed based on Signal to Noise Ratios (SNR) and Compression Ratios.